Analisis Bibliometrik dengan VOSviewer: Penelitian dalam Audit Manajemen Lingkungan - Bunga Puji Lestari; Vania Adisty Hasibuan; Dinda Mustika Triwardani; Sri Wulan Saputri; Siti Rodiah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Environmental management audits are an important element in managing the company's sustainability and performance. The main objective is to analyze the development of research on environmental management audits using a bibliometric approach with the VOSviewer tool. The study identifies key trends, collaboration patterns, and evolving themes in the environmental audit-related literature. Publication data was obtained from Google Scholar using the keyword